PLURALITAS AGAMA SEBAGAI MEDIA INTEGRASI SOSIAL (Ikhtiar Memperkokoh Persatuan Dan Kesatuan Bangsa) - Amir Tajrid (Religia, 2009)
At present, religious community faces big theological challenge in defining themselves in religious plurality. In Indonesian context, the biggest theological challenge sometimes happens in internal religious community. In this context, it is also understood that the meetings among religious figures to dialogue their communities’ problems. At individual level, their relationship seems harmony, but at theological level, it still experiences big enough obstacle, either at religious elite or laity. At this level, religious truth is conditioned be something absolute and not plural. Therefore, religious plurality view becomes something urgent as a medium of social integration in consolidating framework of nation unity